Development and Implementation of a Web-Based Citizen Data Management System for Village Administration: A Case Study of Keboan Anom Village, Sidoarjo, Indonesia - Pradita Maulidya Effendi; Dita Nurmadewi (Indonesian Journal of Cultural and Community Development, 2023)
This research focuses on the development and implementation of a web-based citizen data management system in Keboan Anom Village, Sidoarjo, Indonesia. The aim of the study is to enhance the efficiency and effectiveness of citizen data recording and management processes. The System Development Life Cycle (SDLC) Waterfall model is employed as the methodology for system development, ensuring an organized and systematic approach. Data collection involves semi-structured interviews and unstructured observations, targeting the village's RT 01 (neighborhood association) officials. The application features two key functions: citizen registration, including permanent and non-permanent residents, and a comprehensive data summary. Access to these functions is limited to the RT Secretary and the RT Chairman. The implementation of the system provides improved data management and financial tracking capabilities, enabling simplified reporting. The web-based platform ensures accessibility for RT officials and residents with internet connectivity. Black box testing confirms the functionality of the website and its compliance with expected outputs. The results demonstrate that the application supports the transformation of Keboan Anom Village into a more efficient and technologically connected Digital Village. Future research is suggested to examine community participation levels in using the citizen data management application and its impact on decision-making and overall village governance, incorporating participatory approaches to understand the perspectives and active involvement of Keboan Anom Village residents. Highlight: Efficient citizen data management: The development of a web-based application for citizen data management in Desa Keboan Anom enables efficient recording and documentation of resident information, improving data accuracy and accessibility. Technological transformation: The implementation of the web-based system contributes to the realization of a Digital Village concept, facilitating efficient and technology-connected administration in Desa Keboan Anom, Sidoarjo. Participatory approach: Future research should focus on evaluating community participation levels and the impact of the citizen data management application on decision-making and overall village governance, utilizing a participatory approach to gain insights and foster active involvement of Keboan Anom Village residents. Keyword: Keboan Anom Village, Citizen Data Management, Web-Based Application, Efficiency, Participatory Approach